Utilization prospects of eggshell powder in sustainable construction material – A review - Sathiparan, N. (Elsevier, 2021)
With the rapid growth of infrastructure development, the demand for construction materials has also increased. Cement is one of the materials used widely around the world. Using nonrenewable resources in the production of cement and the CO2 emissions has created signiﬁcant environmental issues. Using waste materials as a partial or full replacement for cement is one of the practical solutions available. The conversion of waste materials into a cement replacement may reduce the environmental issues caused by the open dumping of the waste. Eggshell is a waste material that can be obtained from restau- rants, bakeries and households. If effective uses for eggshell can be found, it would create an opportunity for a sustainable solution. This paper presents the latest studies on the use of eggshell powder in con- struction materials such as concrete, cement mortar, brick, alkali-activated binder and a soil stabilizer. The physical and chemical properties of the eggshell powder and the factors that inﬂuence the character- istics of eggshell power were also analyzed. The results indicate that the characteristics of cementitious materials improved. Speciﬁcally, a 10–15% cement replacement with eggshell powder results in strength development comparable to the control. Several studies have shown the potential of using eggshell pow- der as a stabilizer for soil and brick to improve its mechanical properties. Eggshell powder is therefore energy and cost-effective solution to the problem of sustainable construction materials.
Keywords: Cementitious materials; Cement; Eggshell powder; Sustainability